Tremor pattern differentiates drug-induced resting tremor from Parkinson disease. (April 2016) - Nisticò, R.; Fratto, A.; Vescio, B.; Arabia, G.; Sciacca, G.; Morelli, M.; Labate, A.; Salsone, M.; Novellino, F.; Nicoletti, A.; Petralia, A.; Gambardella, A.; et al.
Abstract: Objective: DAT-SPECT, is a well-established procedure for distinguishing drug-induced parkinsonism from Parkinson's disease (PD). We investigated the usefulness of blink reflex recovery cycle (BRrc) and of electromyographic parameters of resting tremor for the differentiation of patients with drug-induced parkinsonism with resting tremor (rDIP) from those with resting tremor due to PD. Methods: This was a cross-sectional study. In 16 patients with rDIP and 18 patients with PD we analysed electrophysiological parameters (amplitude, duration, burst and pattern) of resting tremor. BRrc at interstimulus intervals (ISI) of 100, 150, 200, 300, 400, 500 and 750 msec was also analysed in patients with rDIP, patients with PD and healthy controls. All patients and controls underwent DAT-SPECT. Results: Rest tremor amplitude was higher in PD patients than in rDIP patients ( p < 0.001 ), while frequency and burst duration were higher in rDIP than in PD ( p < 0.001, p < 0.003, respectively). Resting tremor showed a synchronous pattern in all patients with rDIP, whereas it had an alternating pattern in all PD patients ( p < 0.001 ). DAT-SPECT was normal in rDIP patients while it was markedly abnormal in patients with PD. Conclusions: In the absence of DAT-SPECT, the pattern of resting tremor can be considered a useful investigation for differentiating rDIP from PD. Highlights: We evaluated resting tremor in patients with DIP and in those with rPD. Electrophysiologic characteristics of resting tremor differed between PD and rDIP. Pattern of resting tremor accurately differentiated rDIP patients from those with PD. R2 recovery at ISI 100 ms was different between PD patients and rDIP. R2 recovery distinguished with an accuracy of 82.3% PD from rDIP.